Citizen science can enhance strategies to detect and manage invasive forest pests and pathogens - Hulbert, Joseph M.; Hallett, Richard A.; Roy, Helen E.; Cleary, Michelle (Frontiers in Ecology and Evolution, 2023)
Incorporating a citizen science approach into biological invasion management strategies can enhance biosecurity. Many citizen science projects exist to strengthen the management of forest pest and pathogen invasions within both pre- and post-border scenarios. Besides the value of citizen science initiatives for early detection and monitoring, they also contribute widely to raising awareness, informing decisions about eradication and containment efforts to minimize pest and pathogen spread, and even finding resistant plant material for restoration of landscapes degraded by disease. Overall, many projects actively engage citizens in the different stages of forest pest and pathogen invasions, but it is unclear how they work together across all stages of the entire biological invasion process to enhance biosecurity. Here we provide examples of citizen science projects for each stage of the biological invasion process, discuss options for developing a citizen science program to enhance biosecurity, and suggest approaches for integrating citizen science into biosecurity measures to help safeguard forest resources in the future.